Analisa Pengaruh Pemanfaatan Hotspot Terhadap Indek Prestasi Mahasiswa STMIK Sinar Nusantara Surakarta Dengan SPSS & Analisa SWOT - Bambang Satrionugroho, Kustanto (Jurnal Ilmiah SINUS, 2014)
College, especially in STMIK Sinar Nusantara Surakarta, learning via the Internet is already a part of the duty a lecturer and students. The purpose of this research was to find out the effect facility of hotspots that have been provided by academic toward index of achievement that obtainable a student STMIK Sinar Nusantara Surakarta. In this research using the method: study design, data collection, sampling, determination of outcome indicators, data processing. By using bivariate analysis and Linear Regression Correlations show that hotspots on campus have an influence on student achievement index by 41%, while 59% is influenced by other vaktor not examined. While the results of the SWOT analysis shows that the development of a hotspot getting strength enough reliable from facilities owned by the current institution and supported by instructional discourse model of e-learning is done by lecturers. Keywords: Analysis, Hotspot, achievement index